Effect of Yeast : Saccharomyces cerevisiae and Marine Yeast as probiotic supplement on performance of poultry - I Putu Kompiang (Indonesian Center for Animal Research and Development (ICARD), 2002)
An experiment had been conducted to evaluate the effect of marine yeast and Saccharomyces cerevisiae (Sc) as probiotic supplement on poultry performance. Marine yeast isolated from rotten sea-weed and commercial Saccharomyces cerevisiae were used. Evaluation was conducted by comparing performance of broiler chicken supplemented with marine yeast or Sc, which were given through drinking water (5 ml/l) to negative control (feed without antibiotic growth promotor/GPA), positive control (feed with GPA), and reference commercial probiotic. Forty DOC broiler birds were used for each treatment, divided into 4 replicates (10 birds/replicate) and raised in wire cages for 5 weeks. Body weight and feed consumption were measured weekly and mortality was recorded during the trial. The results showed that there were no significant difference on the birds performance among marine yeast, Sc, positive control and probiotic reference control treatments. However their effects on bird performance were better (P<0.05) than treatment of negative control. It is concluded that marine yeast or Saccharomyces cerevisiae could replace the function of antibiotic as a growth promotant. Key words : Marine yeast, Saccharomyces cerevisiae, probiotic, GPA, poultry